2013
DOI: 10.3945/jn.113.178772
|View full text |Cite
|
Sign up to set email alerts
|

The Human Milk Metabolome Reveals Diverse Oligosaccharide Profiles

Abstract: Breast milk delivers nutrition and protection to the developing infant. There has been considerable research on the high-molecular-weight milk components; however, low-molecular-weight metabolites have received less attention. To determine the effect of maternal phenotype and diet on the human milk metabolome, milk collected at day 90 postpartum from 52 healthy women was analyzed by using proton nuclear magnetic resonance spectroscopy. Sixty-five milk metabolites were quantified (mono-, di-, and oligosaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
251
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(272 citation statements)
references
References 82 publications
15
251
3
3
Order By: Relevance
“…Infants that are breast fed by secretor mothers are protected from moderate-to-severe diarrhea caused by a variety of enteric pathogens, ostensibly the HMOs act as decoy binding sites for the pathogens thus reducing access to epithelial binding sites [72,75]. This is possible because secretor mothers produce more free milk oligosaccharides in terms of both structural diversity and total amount produced compared to non-secretor mothers [72,73]. However, there is a great deal of functional redundancy in lactation.…”
Section: Direct Effects Of Glycans On Intestinal Microbiotamentioning
confidence: 95%
See 1 more Smart Citation
“…Infants that are breast fed by secretor mothers are protected from moderate-to-severe diarrhea caused by a variety of enteric pathogens, ostensibly the HMOs act as decoy binding sites for the pathogens thus reducing access to epithelial binding sites [72,75]. This is possible because secretor mothers produce more free milk oligosaccharides in terms of both structural diversity and total amount produced compared to non-secretor mothers [72,73]. However, there is a great deal of functional redundancy in lactation.…”
Section: Direct Effects Of Glycans On Intestinal Microbiotamentioning
confidence: 95%
“…Lewis blood type and secretor status determine the structure and concentration of fucosylated oligosaccharides providing a clear example of how maternal genotype can affect milk composition and, subsequently, the infant gut microbiota [72,73]. Women who possess a functional FUT2 gene, i.e., who express detectable levels of α-1,2-fucosyltransferase, in body fluids such as tears, saliva, and milk are called secretors.…”
Section: Direct Effects Of Glycans On Intestinal Microbiotamentioning
confidence: 99%
“…The applicant provided several publications on the 2'-FL content in human milk in relation to secretorand Lewis-blood group status (Thurl et al, 1997;Galeotti et al, 2012Galeotti et al, , 2014, ethnicity (Erney et al, 2000;Musumeci et al, 2006), lactation period (Coppa et al, 1999;Erney et al, 2000;Sumiyoshi et al, 2003;Asakuma et al, 2008;Leo et al, 2010;Bao et al, 2013), preterm birth (Nakhla et al, 1999;Gabrielli et al, 2011), and in mature milk (Chaturvedi et al, 1997(Chaturvedi et al, , 2001aErney et al, 2000Erney et al, , 2001Sumiyoshi et al, 2003;Morrow et al, 2004;Leo et al, 2010;Thurl et al, 2010;Asakuma et al, 2011;Coppa et al, 2011;Galeotti et al, 2012;Smilowitz et al, 2013;Hong et al, 2014). The concentration of 2'-FL in breast milk appears to depend on the lactation period, with higher levels reported in colostrum and decreased levels observed thereafter (Erney et al, 2000).…”
Section: Safety Of 2'-o-fucosyllactosementioning
confidence: 99%
“…It is interesting to note that, although HMOs are intrinsic to mother's milk, the composition is not universal. One study that investigated the constituents of milk samples from 52 mothers at 34-38 wk of gestation showed that, although there were a number of conserved metabolites between subjects, there was great variability in the types of oligosaccharides present (44).…”
Section: Management Strategiesmentioning
confidence: 99%
“…There are many sugars present in human milk, the most abundant components being lactose and oligosaccharides (44). The gut microbial composition is influenced by humanmilk oligosaccharides (HMOs), which are an abundant and diverse family of glycans.…”
Section: Management Strategiesmentioning
confidence: 99%